After Keats: The Return of Joseph Severn to England in 1838 - Scott, Grant (Romanticism on the Net)

(untitled) (Université de Montréal, 2005)
AbstractThe recent discovery of hundreds of unpublished letters from Joseph Severn to his wife Elizabeth complicates our standard view of “the Friend of Keats.” The new letters emphasize Severn’s own career as a painter who exhibited regularly at the Royal Academy and highlight his work in fresco and portraiture as well as religious and historical subjects. This essay discusses Severn’s important visit to England in 1838, offering annotated transcripts of two new letters from this time. These letters afford us valuable new information about Severn’s visit, his meetings with key patrons and friends and his motivations for returning to England. The complete series of sixteen letters from the summer of 1838 invites us to revise our conception of Severn’s character and his relationship with Keats.